Penguatan Nilai Agama dalam Menumbuhkan Sikap Moderasi Beragama di SMA Negeri 1 Natal - Nursatia Ritonga; Muhammad Ikbal; Rohman (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This research aims to determine the strengthening of religious values ​​in fostering an attitude of religious moderation at SMA Negeri 1 Natal and further to explain the supporting and inhibiting factors for strengthening religious values ​​carried out by teachers in fostering an attitude of religious moderation at SMA Negeri 1 Natal. This research uses qualitative descriptive. The research data sources are religious teachers and students of SMA Negeri 1 Natal. The data collection techniques used are through observation, interviews and documentation. The results of research on Strengthening Religious Values ​​in Cultivating Attitudes of Religious Moderation at SMA Negeri 1 Natal are that teachers provide strengthening of religious moderation to their students through religious education programs and extracurricular activities such as Islamic Spirituality (ROHIS). The values ​​used in strengthening religious moderation at SMA Negeri 1 Natal are Tawassuth (taking the middle path), Tawazzun (balanced), I'tidal (fair/upright), Tasamuh (tolerance), Muswah, Shura (deliberation). The supporting factor felt by teachers at SMA Negeri 1 Natal is getting good support from the school and other teachers. Meanwhile, the inhibiting factor felt by teachers at SMA Negeri 1 Natal is the large number of students so it is not possible to control all students to perform congregational prayers.